Improvement of the Performance Appraisal System at PT XYZ - Roza Muhammad Shidqi; Dermawan Wibisono (Journal of Economics and Business UBS, 2023)
PT XYZ, a leading gaming company in Indonesia, underwent strategic transformation in 2023 - shifting focus to become a multifaceted gaming services provider in Southeast Asia. This research analyzed PT XYZ's performance appraisal system, identified gaps, and recommended improvements aligned with its renewed vision. The annual appraisal comprises cultural and competence reviews using 360-degree feedback. Self-assessments are veryfied before submission to HR, which produces mapping leading to Talent Mapping. Research objectives were assessing strengths/weaknesses, identifying gaps, and recommending practical enhancements tailored to PT XYZ. Diagnostic qualitative methodology examined the system. Results revealed fragmented data, scalability issues, dynamic criteria, subjectivity, limited feedback and recognition, and incomplete evaluations - despite a structured cultural/competence review. Proposed improvements include modernizing tools, enabling continuous feedback, and refining indicators reflecting industry demands. Recommendations aim to simplify appraisals, boost engagement, reduce subjectivity, and enable holistic evaluation - ultimately enhancing motivation, retention, and strategic alignment. Impact lies in potential to position PT XYZ as a leading regional gaming outsourcer. This contributes insights on optimizing appraisals for the Indonesian gaming industry. By addressing gaps and aligning systems to industry dynamics, recommendations can foster more engaging and effective evaluations at PT XYZ.